The Effect of Post-Weld Heat Treatment Temperature on Microstructure and Mechanical Properties of FCAW-Welded SS400 Steel - Edo Aprianto; Haftirman Haftirman (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
Low-carbon structural steels, such as SS400, are widely used in shipbuilding because of their good weldability, ductility, and adequate strength. However, welding introduces residual stresses and microstructural transformations that may reduce the mechanical performance of welded joints; therefore, post-weld heat treatment (PWHT) is important for improving weld integrity. This study investigated the effect of PWHT temperature on the microstructural evolution and mechanical properties of SS400 steel welded using flux-cored arc welding (FCAW) in the 3G and 4G positions. Welded specimens were subjected to PWHT at 550, 650, and 750°C for 60 min, followed by air cooling, while non-PWHT specimens were used as a reference. Microstructural characterization, hardness testing, and tensile testing were performed to evaluate the mechanical behavior of the welded joints. The base metal and heat-affected zone (HAZ) were predominantly composed of ferrite and pearlite under all conditions, whereas the weld metal exhibited martensite and Widmanstätten ferrite in the lower PWHT range. Among the investigated conditions, PWHT at 550 °C produced the most favorable mechanical response, achieving the highest tensile strength of 556 MPa and average hardness values of 191.3 HV in the base metal, 189.3 HV in the HAZ, and 179 HV in the weld metal. The results demonstrate that PWHT temperature significantly influences phase evolution and mechanical performance, with 550°C identified as an effective treatment condition for improving the mechanical reliability of FCAW-welded SS400 joints.